Comparing General vs. Specialized Educational Programs: Which Approach is Superior? - Aalap Patel; Rahul Chauhan; Andino Maseleno; Aa Hubur (Greenation Research & Yayasan Global Resarch National, 2025)
The article compares general educational programmes and specialized programmes in the key advantages offered by each. Advocates for general educational programs opine that a broad-based education better equips students for success in a rapidly changing job market, while supporters of specialized programmes believe that a more targeted education is more efficient and effective. This article provides an overview of the main arguments on both sides and considers the evidence from empirical studies. The paper concludes that the optimal approach depends on the individual student and their future career aspirations.